The Relationship between Serum Ferritin Levels and Insulin Resistance in Pre- and Postmenopausal Korean Women: KNHANES 2007–2010 - Kim, Min Kyoung (PLoS One, 2016)
BACKGROUND: Serum ferritin levels increase in postmenopausal women, and they are reported to be linked to major health problems. Here, we investigated the association between serum ferritin levels and insulin resistance (IR) in postmenopausal women. METHODS: A total of 6632 healthy Korean women (4357 premenopausal and 2275 postmenopausal) who participated in the Korean National Health and Nutrition Examination Survey (KNHANES) in 2007–2010 were enrolled in the study. Serum ferritin values were divided into six groups for the premenopausal and postmenopausal groups. IR and obesity indices were evaluated according to the six serum ferritin groups. Statistical analysis was carried out using SAS software, version 9.2 (SAS Institute Inc., Cary, NC, USA). RESULTS: The association between the IR indices and ferritin groups had a higher level of statistical significance in the postmenopausal group than in the premenopausal group. In addition, for the postmenopausal group, the estimates increased significantly in the sixth ferritin group compared to those in the first ferritin group. However, the association between the obesity indices and ferritin levels was not significantly different between the premenopausal and postmenopausal groups. CONCLUSION: Elevated serum ferritin levels were associated with an increased risk of insulin resistance in postmenopausal women.